Effect of glutaraldehyde and ferric sulfate on shear bond strength of adhesives to primary dentin - Prabhakar A; Bedi S (Wolters Kluwer Medknow Publications, 2008)
Aim: The present study was undertaken to evaluate the effect of alternative pulpotomy agents such as glutaraldehyde and ferric sulfate on the shear bond strength of self-etch adhesive systems to dentin of primary teeth. Materials and Methods: Eighty human primary molar teeth were sectioned in a mesiodistal direction and divided into experimental and control groups. Lingual dentin specimens in experimental groups were treated with glutaraldehyde and ferric sulfate. Buccal surfaces soaked in water served as control group. Each group was then divided into two groups based on the adhesive system used: Clearfil SE Bond and Adper Prompt L-Pop. A teflon mold was used to build the composite (Filtek Z-250) cylinders on the dentinal surface of all the specimens. Shear bond strength was tested for all the specimens with an Instron Universal Testing Machine. The failure mode analysis was performed with a Scanning Electron Microscope (SEM). Results: The results revealed that glutaraldehyde and ferric sulfate significantly reduced the shear bond strength of the tested adhesive systems to primary dentin. Clearfil SE Bond showed much higher shear bond strength than Adper Prompt L Pop to primary dentin. SEM analysis revealed a predominant cohesive failure mode for both adhesive systems. Conclusion: This study revealed that the pulpotomy medicaments glutaraldehyde and ferric sulfate adversely affected the bonding of self-etch adhesive systems to primary dentin.